1995
DOI: 10.1152/ajpheart.1995.269.4.h1370
|View full text |Cite
|
Sign up to set email alerts
|

Role of bradykinin in cardiac functional protection after global ischemia-reperfusion in rat heart

Abstract: We have reported that cardiac preconditioning against ischemia-reperfusion (IR) can be induced by transient ischemia (TI) and alpha 1-adrenoreceptor stimulation, both mediated by protein kinase C (PKC) (Mitchell, M., X. Meng, C. Parker, E. Brew, A. Harken, and A. Banerjee. Circ. Res. 76: 73-81, 1995). Our study objective was to explore the mechanism of endogenous preconditioning and address the role of PKC activation in bradykinin-mediated cardiac functional protection. Isolated rat heart was used to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 0 publications
2
44
0
2
Order By: Relevance
“…Goto, et al have shown in the isolated rabbit heart that PKC inhibitors completely abolished the infarct-sparing effect of exogenously administered BK, 4) and Bugge and Ytrehus reported that PKC blockade markedly reduced the infarct-inhibiting effect of BK in the isolated rat heart. 5) In a study that used the recovery of ventricular function as an endpoint, a PKC inhibitor completely blocked the protective effect of exogenous BK 26) as shown also by our results. A number of studies have sought to elucidate the end-effector of ischemic preconditioning, and have revealed that the mitochondrial K ATP channel is an important mediator.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Goto, et al have shown in the isolated rabbit heart that PKC inhibitors completely abolished the infarct-sparing effect of exogenously administered BK, 4) and Bugge and Ytrehus reported that PKC blockade markedly reduced the infarct-inhibiting effect of BK in the isolated rat heart. 5) In a study that used the recovery of ventricular function as an endpoint, a PKC inhibitor completely blocked the protective effect of exogenous BK 26) as shown also by our results. A number of studies have sought to elucidate the end-effector of ischemic preconditioning, and have revealed that the mitochondrial K ATP channel is an important mediator.…”
Section: Discussionsupporting
confidence: 85%
“…18) Previous experimental studies in the isolated rat heart have demonstrated that pretreatment with BK for 5 to 10 minutes before the initiation of global ischemia improved postischemic left ventricular function in the isolated rat heart. [26][27][28] Similarly, the work of Feng, et al on the isolated rabbit heart has shown that the infusion of BK for 10 minutes and cardioplegic arrest with BK-enriched St. Thomas' cardioplegia solution before the initiation of global ischemia improved the recovery of ventricular function. 22) In line with these studies, the present results demonstrate that pharmacological preconditioning with two cycles of BK infusion can protect the heart subjected to ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, a recently reported notable effect of bradykinin is that bradykinin is protective in some cases of reperfusion injury of cardiac stenosis or thrombosis (81). Also, a recent interesting report (82) is a study with the mixed-gene kininogen deficient rats, which were produced by back-crossing kininogen-deficient B / N-Ka and normal B / N rats with genetically susceptible Lewis rats for 5-generations.…”
Section: Role Of the Kallikrein-kinin System In Inflammatory Exudate mentioning
confidence: 99%
“…10,72,75,76,[103][104][105][106][107][108][109] This protective phenomenon has been termed ischemic preconditioning. 103 Ischemic preconditioning can be mimicked pharmacologically by adenosine, 110,111 alpha-adrenergic agonists, 104 bradykinin, 112 and ATPsensitive potassium channel (K ATP ) agonists. 110 Our group has proposed that the protection afforded by adenosine preconditioning against cardiac ischemia reperfusion injury may be due to reduced TNF production.…”
Section: 30mentioning
confidence: 99%